Application of Incoterms in Logistics - Ismailova, Madina (2020)
This thesis provides analytical data on how the application of Incoterms® would change the logistics system in Kazakhstan. The thesis presents theoretical and practical data on what are Incoterms®, how logistics influence country’s businesses and economy, what are other efficient tools and methods in the supply chain of companies and finally what is the current situation of logistics in Kazakhstan.